Married and no sex anymore: mbulu as a pastoral problem in Mzimba in northern Malawi - Kamwela, Bonet Byton (Luviri Press, 2020)
This study focusses on the traditional belief of the district of Mzimba, which is situated in the northern part of Malawi. Women who reach menopause who believe in mbulu refuse to have sex with their husbands, They believe that un-used sperms come out during menstruation, but since the period is past, these sperms will remain in the womb and grow into living creatures causing the woman to swell the stomach and then later die. The author, a Reverend and MA student at Mzuzu University, details the belief and its effect on society in Mzimba